(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2025)
Laser technology has a significant impact on our lives in numerous ways. Its contributions to the fields of medicine and dentistry are significantly impacting patient care and well-being. Gingivectomy, pulpotomy, frenectomy, cavities, cysts, tumors, ulcers, and other soft and hard tissue procedures have all been transformed by laser technology, which has also transformed dental care. It has become a fascinating technology in dentistry, and it is used in various clinical practices for multiple procedures. Because of their significant absorption in haemoglobin, near-infrared (NIR) wavelengths have proven excellent for multiple soft tissue treatments. This article provides a comprehensive overview of NIR lasers and their applications in dentistry, focusing on how these tools may precisely cut, coagulate, ablate, or vaporize particular tissues while improving efficiency, specificity, comfort, and ease of use.